New aspects of intra-industry trade between ASEAN5 and China / Chin Mui Yin - Chin, Mui Yin (2013)
This study analyzes new aspects of intra-industry trade relationship between ASEAN5 countries and China in manufacturing sub-sectors from 1993 to 2009. China is chosen in this study as she has emerged as the largest trading partner of ASEAN in 2009 and the trade volume among them has increased gradually over the years. However, the changes of trade balance of the respective ASEAN5 countries from surplus to deficit or vice-versa have raised the problem on whether ASEAN5-China trade is dependent on inter-industry or intra-industry trade (IIT). Besides, China with rich labour endowment has augmented her specialization and induced fundamental changes in the ASEAN5-China trade structure. The processing trade has become increasingly important in China’s trade. It is also noticeable that macroeconomic variables will provide different dynamic impact on ASEAN5-China bilateral trade. In addition, the threat of passing the pain of external shock to other trading partners in regional trade has raised the concern of value chain in enhancing and sustaining bilateral trade between ASEAN5 countries and China. As such, resilient products for each ASEAN5 country must be identified in order to enhance and sustain the bilateral trade between ASEAN5 countries and China. To produce a comprehensive study, both decomposition–type threshold based method and advanced spatial panel econometric technique are employed. The results of the decomposition-type threshold based method reveal that IIT between each ASEAN5 country and China is generally significant, particularly SITC 7 but the intensity of IIT varies among ASEAN5 countries. Singapore, Malaysia and Thailand are prone to IIT while the intensity of IIT for Indonesia and Philippines are relatively low. Besides, vertical intra-industry trade (VIIT) has dominated IIT between each ASEAN5 country and China across manufacturing sub-sectors. This confirms that IIT between the two regions is processing trade in nature. This study then applied spatial panel econometric technique to estimate the explanatory variables of VIIT for each manufacturing sub-sector. The estimated results reveal that the impact of each explanatory variable is varied. FDI is significant in all manufacturing sub-sectors except for SITC 8 while DGDP serves as catalyst in stimulating VIIT between ASEAN5 countries and China in SITC 6 and 7. Furthermore, the spatial interaction effects are found to be present in each manufacturing sub-sector. VIIT is then further decomposed into high value of vertical intra-industry trade (HVIIT) and low value of vertical intra-industry trade (LVIIT). The HVIIT products provide the synergy in strengthening the trade relationship between the two countries and otherwise for LVIIT products. The decomposition results reveal that the focal points of Singapore are in all manufacturing sub-sectors except SITC 8; Malaysia on SITC 5 and SITC 6; Thailand and Indonesia on SITC 7. Although Philippines focuses on SITC 7, her trade ties with China is relatively volatile throughout the study period. Hence, Philippines needs to reshuffle her trade policies to enhance the sustainability of trade with China. Besides, the analysis has identified the resilient products in each manufacturing sub-sector where value-adding by ASEAN5 countries are consistently possible in their bilateral trade with China.